2011
DOI: 10.1002/ibd.21522
|View full text |Cite
|
Sign up to set email alerts
|

Self-reported adherence to medical treatment prior to and during pregnancy among women with ulcerative colitis

Abstract: Adherence was high despite fear of a negative effect on fertility or the fetus. Counseling predicted higher adherence. This may be important because our study suggests an increase in UC activity during pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
66
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(69 citation statements)
references
References 46 publications
1
66
1
1
Order By: Relevance
“…Previous research conducted in Australia showed that women with IBD were fearful of the effects of medication upon pregnancy with 30% specifically fearing congenital anomalies 38 and as many as 84% fearing some adverse effect upon the pregnancy 14 . We also have data from Denmark where studies in UC and CD have demonstrated that not only do women with IBD fear the effects of their medications, but this also leads to reduced adherence 20,21 . Since all of these studies were based upon questionnaires, and therefore are susceptible both to recall and response biases, the data they provided on medication usage by women with IBD during pregnancy may be less reliable than the prospectively recorded prescription data which we have analysed despite the fact that we are unable to assess compliance.…”
Section: Interpretation In the Context Of Previous Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Previous research conducted in Australia showed that women with IBD were fearful of the effects of medication upon pregnancy with 30% specifically fearing congenital anomalies 38 and as many as 84% fearing some adverse effect upon the pregnancy 14 . We also have data from Denmark where studies in UC and CD have demonstrated that not only do women with IBD fear the effects of their medications, but this also leads to reduced adherence 20,21 . Since all of these studies were based upon questionnaires, and therefore are susceptible both to recall and response biases, the data they provided on medication usage by women with IBD during pregnancy may be less reliable than the prospectively recorded prescription data which we have analysed despite the fact that we are unable to assess compliance.…”
Section: Interpretation In the Context Of Previous Literaturementioning
confidence: 99%
“…Based on this evidence as well as the known tendency of IBD to flare upon cessation of disease suppressing medication and the recognised excess of other adverse pregnancy outcomes which may be driven by disease activity 14 , a number of guidelines have been written [15][16][17][18][19] . These propose that women should not cease drug treatment that is maintaining their IBD in remission for the purpose of becoming pregnant or protecting a pregnancy, yet very recent studies indicate that women remain fearful of the potential harm of their drugs during pregnancy 20,21 .…”
Section: Introductionmentioning
confidence: 99%
“…The first patient had a severe form of disease, diagnosed awhile ago, with good response to combined mesalamine therapy, but was noncompliant. Usually, the rate of noncompliance increases with pregnancy due to the patient's prejudice over medications and fear of negative effects on offspring [12,13] . In a population-based study, Nielsen et al [13] found non-adherence to therapy in 28% of women during pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…7 These misperceptions contribute to suboptimal medication adherence before and during pregnancy, thereby increasing the risk of disease relapse and adverse pregnancy outcomes. 8 Despite misperceptions, IBD patients are information hungry. 9 The combination of low knowledge and desire for more information is an ideal scenario for patient education and counseling.…”
mentioning
confidence: 99%
“…The authors note the extremely high rate of correct IBD medication adherence, with adherence rates in both groups exceeding the 60%-75% adherence observed in prior studies. 8 Although drug levels were measured in some patients, correct adherence was not defined. This raises the question of whether the common phenomenon of covert dose reduction may have contributed to breakthrough disease activity.…”
mentioning
confidence: 99%